2016
DOI: 10.1097/acm.0000000000001024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reasoning Tasks and Resident Physicians: What Do They Reason About?

Abstract: Results suggest that the use of clinical reasoning tasks occurs in a varied, not sequential, process. The authors provide suggestions for strengthening the framework to more fully encompass the spectrum of reasoning tasks that occur in residents' clinical encounters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…Congruent assignment of internists’ characteristics increased significantly from S1 to S12 with the most congruent assignment of the characteristic “… are the keenest thinkers of all doctors” by 31.1% in S12. During their undergraduate studies, medical students become increasingly exposed to clinical reasoning processes and especially observe residents in their daily practice of how they reason and what they reason about [ 35 ]. This might also explain why “… ponder everything.” and “… are hesitant and have a ‘wait and see attitude’.” reached high assignment scores as well.…”
Section: Discussionmentioning
confidence: 99%
“…Congruent assignment of internists’ characteristics increased significantly from S1 to S12 with the most congruent assignment of the characteristic “… are the keenest thinkers of all doctors” by 31.1% in S12. During their undergraduate studies, medical students become increasingly exposed to clinical reasoning processes and especially observe residents in their daily practice of how they reason and what they reason about [ 35 ]. This might also explain why “… ponder everything.” and “… are hesitant and have a ‘wait and see attitude’.” reached high assignment scores as well.…”
Section: Discussionmentioning
confidence: 99%
“…The only study exploring their use in clinical practice involved a think-aloud protocol of three diagnostic, video-based scenarios (McBee et al 2015). And, while several new insights were gained about the tasks themselves and their relationships to each other, the study findings may not have been fully reflective of the use of reasoning tasks in real world settings.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, important tasks identified during clinical encounters have included framing the problem, diagnosis, management, and reflection. 5,6 However, physicians generally use intuitive reasoning and omit reflective reasoning in their routine mode of thought. 7 As the physician processes the initial history and exam, he or she begins to form a problem representation and an initial diagnosis and plan for further workup and treatment.…”
Section: Discussionmentioning
confidence: 99%